Farmers’ Perception on Pestilence and Management of Chinese Citrus Fly, Bactrocera minax (Enderlein) (Diptera: Tephritidae) in Citrus Orchards of Nepal - Adhikari, D.; Thapa, R.B.; Joshi, S.L.; Du, J.J. (Journal of Agriculture and Environment, 2022)
This study, during period of 2018 and 2019, was conducted with an objective of assessing the farmers’ perspective on the pestilence of B. minax on their citrus orchards and following thereby its pest management measures in the selected eight citrus growing districts of Nepal. Respondent citrus growers were male dominated (75.8%) where Brahmin and Chhetri castes (54.3%) were dominantly involved in the citrus cultivation in the survey districts. Only 25.7% respondent citrus growers had above school level education. The highest reported land holding area, 2.35 ha, was in Sankhuwasabha district followed by Dhankuta (1.72 ha) and Syanjya (1.67 ha). According to the respondents, an average of 234.12 mandarin trees in Syanjya, 159.60 sweet orange trees in Sindhuli, 9.68 lemon trees in Sindhuli, and 11.83 lime trees in Gulmi were calculated maximum acreage of different citrus fruit trees by the each citrus grower. Among the cultivated Citrus spp., lemon fruit found to be extremely vulnerable to Chinese citrus fly infestation. Chinese citrus fly's maggot infestation peak in fruits in orchards was observed in October in the citrus crop cycle. Twenty citrus dominated districts in Nepal found to be regularly invaded of Chinese citrus fly in citrus particularly in lemon, sweet orange and mandarin.